Government-Private Tertiary Institution Partnerships in Guyana: Strategies, Tools, and Techniques to Mitigate and Balance the Impacts of Brain Drain - Paul (Sr.), Stanley A. V.; Paul (Jr.), Stanley A. V. (Integrated Journal for Research in Arts and Humanities, 2024)
This article examines the imperative for the government of Guyana to partner with private tertiary institutions as a strategic tool to counteract brain drain and mitigate its negative impacts. By exploring traditional and current trends in such partnerships, the study analyzes their effectiveness in retaining highly educated individuals within the country. Various approaches, including financial incentives, professional development programs, and community engagement initiatives, are evaluated. The article provides evidence-based recommendations for policymakers and educational institutions to enhance retention rates, ensuring that the local workforce benefits from high-quality education and training.